2009
DOI: 10.1292/jvms.71.1017
|View full text |Cite
|
Sign up to set email alerts
|

Successful Intensive Insulin Treatment of Type 1 Diabetic Dogs Leads to Restoration of Peripheral Leukocyte Insulin Signaling Gene Expression and Enzyme Activities

Abstract: ABSTRACT. The purpose of this study was to investigate whether intensive insulin treatment of dogs suffering from type 1 diabetes mellitus, resulting in tight glycemic control, could be reflected by changes in peripheral leukocyte metabolism. Specifically, plasma metabolites and enzyme activities were assessed. In addition, quantitative RT-PCR was used to determine changes in insulin signaling gene (insulin receptor substrate (IRS)-1, IRS-2 and phosphatidylinositol 3-kinase (PI3-K) P85) mRNA levels in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Two studies in animals have demonstrated the expression of IRS1 in leukocytes [13, 14] the first, using a one dog and one cat, evaluated by PCR the expression of IRS1 and IRS2, PI3-K, P-85 α in different tissues responsive to insulin and in peripheral leukocytes. The aim was to investigate differences in expression of markers found in both species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies in animals have demonstrated the expression of IRS1 in leukocytes [13, 14] the first, using a one dog and one cat, evaluated by PCR the expression of IRS1 and IRS2, PI3-K, P-85 α in different tissues responsive to insulin and in peripheral leukocytes. The aim was to investigate differences in expression of markers found in both species.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IRS1 and 2 in lymphocytes has not been demonstrated in humans but has been shown in some animal studies [13, 14]. Impairment of IRS2 expression (but not in IRS1) in monocyte cells was demonstrated in first-degree relatives of type 2 DM patients [15] The objective of this study is to determine the expression of IRS1 in peripheral leukocytes (IRS1 cells) of HCV-infected patients and in a control group (blood donors), correlating it with the expression of IRS1 in the liver (IRS1 liver) and the presence of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The role of tight glycemic control in critically ill human and small animal veterinary patients and its effect on GIDM is not completely understood and is frequently contested. There is some evidence that maintaining normoglycemia by intensive insulin therapy in critical illness minimizes feeding intolerance and may improve immune function, but the clinical benefit of this approach has been questioned …”
Section: Pathophysiology Of Gidmmentioning
confidence: 99%